Quality of Reporting and Study Design of CKD Cohort Studies Assessing Mortality in the Elderly Before and After STROBE: A Systematic Review. - Anirudh Rao; Katharina Brück; Shona Methven; Rebecca Evans; Vianda S Stel; Kitty J Jager; Lotty Hooft; Yoav Ben-Shlomo; Fergus Caskey (PLoS ONE)
Background The STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) statement was published in October 2007 to improve quality of reporting of observational studies. The aim of this review was to assess the impact of the STROBE statement on observational study reporting and study design quality in the nephrology literature. Study design Systematic literature review. Setting & population European and North American, Pre-dialysis Chronic Kidney Disease (CKD) cohort studies. Selection criteria for studies Studies assessing the association between CKD and mortality in the elderly (>65 years) published from 1st January 2002 to 31st December 2013 were included, following systematic searching of MEDLINE & EMBASE. Predictor Time period before and after the publication of the STROBE statement. Outcome Quality of study reporting using the STROBE statement and quality of study design using the Newcastle Ottawa Scale (NOS), Scottish Intercollegiate Guidelines Network (SIGN) and Critical Appraisal Skills Programme (CASP) tools. Results 37 papers (11 Pre & 26 Post STROBE) were identified from 3621 potential articles. Only four of the 22 STROBE items and their sub-criteria (objectives reporting, choice of quantitative groups and description of and carrying out sensitivity analysis) showed improvements, with the majority of items showing little change between the period before and after publication of the STROBE statement. Pre- and post-period analysis revealed a Manuscript STROBE score increase (median score 77.8% (Inter-quartile range [IQR], 64.7-82.0) vs 83% (IQR, 78.4-84.9, p = 0.05). There was no change in quality of study design with identical median scores in the two periods for NOS (Manuscript NOS score 88.9), SIGN (Manuscript SIGN score 83.3) and CASP (Manuscript CASP score 91.7) tools. Limitations Only 37 Studies from Europe and North America were included from one medical specialty. Assessment of study design largely reliant on good reporting. Conclusions This study highlights continuing deficiencies in the reporting of STROBE items and their sub-criteria in cohort studies in nephrology. There was weak evidence of improvement in the overall reporting quality, with no improvement in methodological quality of CKD cohort studies between the period before and after publication of the STROBE statement.